1992
DOI: 10.1046/j.1365-313x.1992.t01-41-00999.x
|View full text |Cite
|
Sign up to set email alerts
|

Vicilin with carboxy‐terminal KDEL is retained in the endoplasmic reticulum and accumulates to high levels in the leaves of transgenic plants

Abstract: SummaryGene constructs were designed to test the effect of the endoplasmic reticulum (El?)-targeting signal, KDEL, on the level of accumulation of a foreign protein in transgenic plants. The gene for the pea seed protein vicilin was modified by the addition of a sequence coding for this tetrapeptide at its carboxyl terminus. The altered gene was placed under the control of a CaMV 35s promoter and its expression in the leaves of both tobacco and lucerne (alfalfa) was compared with that of an equivalent vicilin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
1
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(81 citation statements)
references
References 43 publications
7
70
1
3
Order By: Relevance
“…Accounting for the differences in total protein applied to the gel (less soybean total protein was loaded), the VSPβ protein was estimated to have accumulated to 0.5 % of the total soluble protein. This is similar to the highest level of seed storage protein accumulation observed with the ectopic expression of zein [8,9], but remains less than the 1% minimal expression level predicted by Wandelt et al [11] to be needed to directly alter the nutritional quality of the leaves. Although the 0.5% of total soluble protein was too low to alter nutritional value, detection of VSPβ in 45-3-1 allowed monitoring of VSPβ level in leaves and stems during plant development.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Accounting for the differences in total protein applied to the gel (less soybean total protein was loaded), the VSPβ protein was estimated to have accumulated to 0.5 % of the total soluble protein. This is similar to the highest level of seed storage protein accumulation observed with the ectopic expression of zein [8,9], but remains less than the 1% minimal expression level predicted by Wandelt et al [11] to be needed to directly alter the nutritional quality of the leaves. Although the 0.5% of total soluble protein was too low to alter nutritional value, detection of VSPβ in 45-3-1 allowed monitoring of VSPβ level in leaves and stems during plant development.…”
Section: Resultssupporting
confidence: 71%
“…Transgenic expression from the CaMV 35S promoter in tobacco resulted in the formation of these protein bodies containing the zein within vegetative tissues [8,9]. Alternatively, "short-circuiting" the protein-targeting route by addition of an ER retention signal to the storage-protein coding region also increased protein accumulation up to 100× [5,6,10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…The H5 protein was recombinantly expressed alone (H5) or as a fusion with hydrophobin (H5-HFBI) or ELP (H5-ELP) under the control of both the CaMV 35S and USP promoters (Figure 1). Each recombinant protein contained the c-myc tag for downstream detection by Western blot, a His tag for purification by immobilized metal ion chromatography (IMAC) and the KDEL motif at the C-terminal end to retain the protein in the endoplasmic reticulum (ER) [43]. The functionality of all binary vectors was validated by assaying the expression of recombinant proteins in transiently transformed N. benthamiana leaves and confirmed by Western blot (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…N -linked glycans are then transported and modified further in the GA from cis to medial and trans cisternae to form typical plant glycans with the addition of xylose and fucose to the core glycans. In this study, the KDEL motif was used to retain recombinant proteins in the ER [43]. The N -linked glycan profiles of these recombinant proteins showed that leaf-derived H5 and H5-HFBI predominantly possess OMT glycans (70–72%) that supposedly matured in the ER compartment and 27–30% CT glycans with typical plant glycans (GnGnX and GnGnF) (Table 2).…”
Section: Discussionmentioning
confidence: 97%
“…Both wild type and codon-optimized pfa genes were cloned into pCaMterX binary vector [17] under the control of double 35S promoter [29] and Nos terminator [30]. Tobacco secretory signal peptide Pr1b [31] was fused to the N-terminal of the gene and StrepII tag [32] and the ER retrieval tetrapeptide KDEL [33] were fused to the C-terminus of the gene…”
Section: Methodsmentioning
confidence: 99%